Peristiwa Tanjung Priok 1984 (Sebuah Gerakan Sosial) - Kholisya, Umi (CHRONOLOGIA, 2023)
Pancasila is a way of life of the Indonesian people. During its development, the New Order government made Pancasila the only principle. This government policy gave rise to protests by the community, especially Islamic mass organizations. As a result of the reaction of Islamic community organizations (ormas), the government considered that these movements rejected the Pancasila ideology and were dangerous for the unity of the country. One form of reaction to this government policy was the explosion of the 1984 Priok Incident. This incident occurred on September 12 1984. The method used is descriptive analytical historical research which consists of several stages, namely topic selection, source collection (heuristics), source criticism, interpretation, and historiography. The sources used are oral sources and written sources. The 1984 Priok incident cannot be separated from what is stated in the Collective Action Theory, namely a social movement based on certain interests and to achieve its goals, mobilization efforts or activities are carried out, while the nature of the action is reactive. In their efforts to prevent past humanitarian violations from being revealed, those responsible for security (security forces) in the period after the Priok incident tried to approach the victims, tried to cooperate and tried to get guarantees so that the 1984 Priok case would not be brought to court. This guarantee is applied in the form of peace called Ishlah.